Integrasi Kurikulum dan Pembelajaran melalui Optimalisasi Komponen-Komponen Kurikulum - Nursia Nursia; Misbah, Misbah; Dadang Sumarna (FKIP UNSULTRA, 2026)
This study aims to analyze the integration of curriculum and learning through the optimization of curriculum components, including objectives, content, methods, and learning evaluation. Curriculum and learning are two interrelated elements in the education system, where the curriculum serves as a planning guideline, while learning is the actual implementation in the classroom. This study employed a library research method with a descriptive qualitative approach. Data were obtained from various scientific sources, including national and international journals, academic books, and relevant research findings from the past ten years. Data collection techniques were conducted through database searches of Google Scholar, SINTA, and other reputable journals, with selection criteria based on the relevance and novelty of the sources. Data analysis was conducted through the stages of data reduction, data presentation, and systematic conclusion drawing. The study results indicate that the integration of curriculum and learning is largely determined by the alignment between curriculum components. The objectives component serves as the primary direction of learning, the content component determines the relevance of the material, the methods component determines effective learning strategies, and the evaluation component serves as a measuring tool for the achievement of learning objectives. Optimizing these four components has been proven to increase learning effectiveness and encourage the holistic achievement of student competencies. Furthermore, the role of teachers as curriculum implementers is a key factor in ensuring integration between planning and implementation of classroom learning. In the 21st-century era of education, the use of technology and learning innovations is also a crucial support in strengthening the integration of curriculum and learning. Therefore, it can be concluded that optimizing curriculum components is a fundamental strategy in creating effective, meaningful, and relevant learning that meets students' needs.